Pengaruh Disiplin Kerja dan Motivasi Terhadap Kinerja Karyawan di PT. Suryabumi Agrolanggeng - Vika Lidya Sari; Muhammad Ichsan Hadjri; Wita Farla (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of work discipline and motivation on employee performance at PT Suryabumi Agrolanggeng. This study uses a quantitative method with census techniques, where the entire population consisting of 132 employees of the Palm Oil Mill is used as respondents. The instrument used was in the form of a questionnaire, and the data were analyzed by multiple linear regression tests. The results of the study show that simultaneously or partially, work discipline and motivation have a positive and significant effect on employee performance. Based on these results, it can be concluded that the higher the discipline and motivation of employees, the better the performance will be.